ANALYSIS OF THE EFFECT OF FOUNDATION DIMENSIONS ON THE BEARING CAPACITY AND SETTLEMENT OF PILE FOUNDATIONS FOR THE WTP SPAM KOBEMA BENGKULU BUILDING - Nurhaliza; Jinan, Raihanah Naura; Misliniyati, Rena; Hardiansyah; Fikri, Muharram Nur; Amri, Khairul (Jurnal Pensil : Pendidikan Teknik Sipil, 2026)
The Water Treatment Plant (WTP) in the Benteng Kobema Bengkulu Regional Drinking Water Supply System (SPAM), with a capacity of 380 Litres per Second, plays a crucial role in providing clean water to the community. This study aims to analyse the influence of dimensional variations on the bearing capacity and foundation settlement of the WTP building using the Poulos and Davis method, the Reese and Wright method, the Luciano Decourt method, and the finite element method. Based on the results of the Standard Penetration Test (SPT), the influence of variations in shape, namely square with dimensions of 300 mm, 400 mm, and 500 mm, as well as depths of 7m, 9m, 11m, and 13m, affects the bearing capacity and foundation settlement This analysis compares the results of bearing capacity calculations and pile foundation settlement in WTP buildings using several different methods. The analysis results show that the bearing capacity, deflection magnitude, and smallest settlement are below the permitted settlement limit, i.e., less than 10% of the foundation dimensions. The comparison between static and numerical methods, or the Bearing Capacity Ratio (BCR) approaching 1, is more efficient and safer. In this analysis, the BCR value closest to 1 was obtained for a 500 mm foundation using the Reese and Wright method at a depth of 9 m, yielding a bearing capacity of 312.04 tonnes for a single pile and 207.69 tonnes for a pile group.